2011
DOI: 10.1136/thoraxjnl-2011-200717
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal inhibition after injury prevents fibrosis by modulating TGF-β1signalling

Abstract: Background The development of organ fibrosis after injury requires activation of transforming growth factor β1 which regulates the transcription of profibrotic genes. The systemic administration of a proteasomal inhibitor has been reported to prevent the development of fibrosis in the liver, kidney and bone marrow. It is hypothesised that proteasomal inhibition would prevent lung and skin fibrosis after injury by inhibiting TGF-β1-mediated transcription. Methods Bortezomib, a small molecule proteasome inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 41 publications
8
52
2
Order By: Relevance
“…Of note, literature reports a reduction in the amount of TGF-β when the proteasome is directly inactivated by the specific inhibitor MG132 (Tashiro et al, 2003;Mutlu et al, 2012) and our data also confirmed this finding (Fig. S3A,E).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Of note, literature reports a reduction in the amount of TGF-β when the proteasome is directly inactivated by the specific inhibitor MG132 (Tashiro et al, 2003;Mutlu et al, 2012) and our data also confirmed this finding (Fig. S3A,E).…”
Section: Discussionsupporting
confidence: 82%
“…As expected (Tashiro et al, 2003;Mutlu et al, 2012), specific proteasome inhibition by MG132 induced a significant downregulation of TGF-β in high-glucose-treated cells (Fig. S3A,E).…”
Section: ) (B)supporting
confidence: 51%
See 1 more Smart Citation
“…To date, steroids are the most effective and utilized treatment, but new immune-modulatory drugs have been experimented to improve muscle repair by reducing inflammation and fibrosis of DMD animal models as anticytokines (anti-TNFα), 30 IL-6r blockade, 31 TGF-β blocker (suramin and pirfenidone) 32,33 and, more recently, Treg expansion. 13 Several evidences suggested that the proteasome is directly involved in the pathophysiology of organ fibrosis: inhibition of the proteasome could block TGF-β1 induced gene expression in primary human lung fibroblasts from healthy individuals and patients with IPF 34,35 and could reduce lung fibrosis in some animal models. 36,37 Indirectly, fibrosis is augmented by inflammatory pathogenesis that is also influenced by i-proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the degradative arms of the proteostasis network, impaired activation of autophagy has been suggested to contribute to IPF pathogenesis [235,236]. The role of proteasomal protein degradation in IPF development is unknown, but cannot be excluded as proteasome inhibitors have been shown to counteract bleomycin-induced fibrosis in mice [237].…”
Section: Loss Of Proteostasismentioning
confidence: 99%